Aplikasi Pengolahan Zakat Berbasis Web (E-Zakat) - Andriansah Andriansah; Ika Yuniva; Putri Ayu Safitri (Bianglala Informatika, 2019)
Zakat is one of the pillars in the religion of Islam, which means it is obligatory for every Muslim who is able to do it. In reality there are still many Muslims who do not understand the types of zakat, the calculation of zakat, payment and processing of zakat, so that it causes them to forget to pay zakat. Moreover, in this modern era, people prefer things that are fast and practical. And if every Muslim and Muslim want to pay zakat for sure, of course this can help improve the economy of the lower middle class. And of course zakat must be issued and processed according to established rules. Therefore in this study an application was built in the form of a website that could handle various community problems regarding payment and data processing of zakat in this modern era. This website is built with the programming languages HTML, CSS, Javascript and PHP and for its database using MySQL and for its web service using Apache. Keywords: Application, Web, Zakat